Postoperative infection predicts poor survival in locoregionally advanced oral cancer. Issue 10 (5th August 2019) - Mascarella, Marco A.; Azzi, Jayson Lee; da Silva, Sabrina Daniela; Mlynarek, Alex; Forest, Veronique‐Isabelle; Hier, Michael; Richardson, Keith; Sadeghi, Nader
Abstract: Background: We ascertain the association of postoperative infection on survival in patients with locoregionally advanced oral cavity squamous cell carcinoma (OCSCC). Methods: A retrospective study of patients with stage III/IVA OCSCC undergoing curative‐intent surgery was performed. Postoperative infection was considered within 30 days after surgery. Kaplan‐Meier survival curves were used to compare overall survival (OS) in patients with postoperative infection. Cox regression and propensity‐score matching were used to adjust for confounders. Results: Fifty‐four of 114 patients had a postoperative infection. The 5‐year OS in patients with a postoperative infection (24.1%) was lower than those without (65.2%; P  < .0001). Postoperative infection was a negative predictor of OS after adjusting for patient, antibiotic, pathologic, and operative factors; the adjusted hazard ratio for OS was 2.54 (95% confidence interval, 1.27‐5.09). Conclusion: Postoperative infection is a strong negative predictor of OS in patients with OCSCC undergoing ablative surgery.